Corticomedullary differentiation and maturational arrest in thymomas. Issue 4 (18th November 2013) - Ströbel, Philipp; Hartmann, Elena; Rosenwald, Andreas; Kalla, Jörg; Ott, German; Friedel, Godehard; Schalke, Berthold; Kasahara, Masanori; Tomaru, Utano; Marx, Alexander
<x xml:space="preserve">Abstract</x> Aims Morphological complexity hampers the histological classification of thymomas. Our aim was to determine whether the use of novel differentiation and maturation markers of cortical and medullary thymic epithelial cells (cTECs and mTECs) might provide an approach to understanding the underlying biology of these tumours. Methods and results Fifty‐seven thymomas were studied by immunohistochemistry. The cortical markers used were B5T, PRSS16, and cathepsin V. The medullary markers used were CD40, claudin‐4, AIRE, and desmin. Involucrin and cytokeratin 10 were used to study terminal mTEC maturation. Irrespective of histological subtype, most thymomas contained distinct areas with cortical and medullary differentiation. Type B1, type B2 and type AB thymomas showed marked bi‐lineage differentiation, with lack of terminal mTEC maturation in type AB. Type AB thymomas were unique in showing areas where cells with either cortical or medullary differentiation were intimately 'mixed' at the single‐cell level. Type B3 and type A thymomas showed only abortive lineage differentiation and maturation. Conclusions Thymomas show highly characteristic patterns of bi‐lineage TEC differentiation that reflect the histological subtypes recognized by the WHO classification. We hypothesize that thymomas arise from thymic precursor cells with different cortical and/or medullary maturation defects.